2007
DOI: 10.1021/ef060385s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Waxy Gel Formation from Batch Experiments

Abstract: In spite of its importance, wax deposition is still not fully understood, and a reliable physical description of wax deposition is still to be agreed upon. Up to now, the focus in wax studies has been mainly on the radial transport of waxes to the cold wall through molecular diffusion, but other mechanisms that have been cited (and so far neglected) may count on the kinetics of deposit formation. An analysis of the experimental evidence is presented here, leading to the conclusion that an important role may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 36 publications
0
40
0
19
Order By: Relevance
“…While flow loop deposition studies date back several decades (Jessen and Howell, 1958;Cole and Jessen, 1960;Hunt, 1962;Jessen and Mendell, 1970;Mendell and Jessen, 1972;Weingarten and Euchner, 1988) more recent work has focused on the fundamental understanding to the deposition process, as well as the ability to accurately model deposition behavior (Burger et al, 1981;Brown et al, 1993;Creek et al, 1999;Singh et al, 2000;Apte et al, 2001;Singh et al, 2001a,b;Matzain et al, 2002;Paso and Fogler, 2003;Venkatesan and Fogler, 2004;Parthasarathi and Mehrotra, 2005;Merino-Garcia et al, 2007). A survey of such studies shows that four key factors determine the rate and nature of the deposit formed: the flow rate (Weingarten and Euchner, 1988;Creek et al, 1999;Singh et al, 2000), the temperature field, (Cole and Jessen, 1960;Burger et al, 1981;Creek et al, 1999;Singh et al, 2000) the composition of the oil Singh et al, 2001b), and the nature of the surface (Cole and Jessen, 1960;Parks, 1960;Jorda, 1966;Kok and Saracoglu, 2000;Zhang et al, 2002).…”
Section: Background On Wax Depositionmentioning
confidence: 99%
“…While flow loop deposition studies date back several decades (Jessen and Howell, 1958;Cole and Jessen, 1960;Hunt, 1962;Jessen and Mendell, 1970;Mendell and Jessen, 1972;Weingarten and Euchner, 1988) more recent work has focused on the fundamental understanding to the deposition process, as well as the ability to accurately model deposition behavior (Burger et al, 1981;Brown et al, 1993;Creek et al, 1999;Singh et al, 2000;Apte et al, 2001;Singh et al, 2001a,b;Matzain et al, 2002;Paso and Fogler, 2003;Venkatesan and Fogler, 2004;Parthasarathi and Mehrotra, 2005;Merino-Garcia et al, 2007). A survey of such studies shows that four key factors determine the rate and nature of the deposit formed: the flow rate (Weingarten and Euchner, 1988;Creek et al, 1999;Singh et al, 2000), the temperature field, (Cole and Jessen, 1960;Burger et al, 1981;Creek et al, 1999;Singh et al, 2000) the composition of the oil Singh et al, 2001b), and the nature of the surface (Cole and Jessen, 1960;Parks, 1960;Jorda, 1966;Kok and Saracoglu, 2000;Zhang et al, 2002).…”
Section: Background On Wax Depositionmentioning
confidence: 99%
“…The influencing factors of wax deposition include crude oil composition, transportation temperature, temperature difference between oil and pipe wall, flow velocity, flow pattern, material of pipe, deposition time, and so on. Consequently, scholars have researched the problem of wax deposition for a long time; however, the mechanism of wax deposition is still not recognized thoroughly . The concept of ‘aging’ is a good supplement to the traditional wax deposition mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Basically, WCOs are characterized by a specific temperature, which is of extreme importance for scientists and engineers handling with these fluids. When the oil is being extracted from reservoir, the temperature may drop below a certain value (the so called Cloud Point or Wax Appearance Temperature, WAT), at which waxes start to solidify and may deposit on the pipe walls (see for example [25]). The most striking consequence can be seen when a WCO is pumped e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the physical mechanisms involved in wax deposition, apart from one of the first works on this subject [5], a good and critical review can be found in [4] and in [25].…”
Section: Introductionmentioning
confidence: 99%